Highly functionalized piperidines: Free radical scavenging, anticancer activity, DNA interaction and correlation with biological activity - Suvankar Das; Cristiane J. da Silva; Marina de M. Silva; Maria Dayanne de A. Dantas; Ângelo de Fátima; Ana Lúcia T. Góis Ruiz; Cleiton M. da Silva; João Ernesto de Carvalho; Josué C.C. Santos; Isis M. Figueiredo; Edeildo F. da Silva-Júnior; Thiago M. de Aquino; et al. (Journal of Advanced Research, 2018)
Twenty-five piperidines were studied as potential radical scavengers and antitumor agents. Quantitative interaction of compounds with ctDNA using spectroscopic techniques was also evaluated. Our results demonstrate that the evaluated piperidines possesses different abilities to scavenge the radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) and the anion radical superoxide (·O2−). The piperidine 19 was the most potent radical DPPH scavenger, while the most effective to ·O2− scavenger was piperidine 10. In general, U251, MCF7, NCI/ADR-RES, NCI-H460 and HT29 cells were least sensitive to the tested compounds and all compounds were considerably more toxic to the studied cancer cell lines than to the normal cell line HaCaT. The binding mode of the compounds and ctDNA was preferably via intercalation. In addition, these results were confirmed based on theoretical studies. Finally, a linear and exponential correlation between interaction constant (Kb) and GI50 for several human cancer cell was observed.